CESifo World Economic Survey November 2015 - Johanna Garnitz; Gernot Nerb; Klaus Wohlrabe (CESifo World Economic Survey, 2015)
World Economic Climate: World Economic Climate cools down markedly - Economic Expectations: Economic expectations less positive - Inflation: Low inflation expectations, particularly in Europe - Currencies: US Dollar seen as overvalued, but expected to rise further - Interest Rates: Fewer WES experts expect interest rates to rise - Special Topic: Should Greece exit the European Monetary Union?
Keywords: 330